The Moral Psychology of Raceless, Genderless Strangers. (March 2020) - Hester, Neil; Gray, Kurt
Moral psychology uses tightly controlled scenarios in which the identities of the characters are either unspecified or vague. Studies with raceless, genderless strangers help to highlight the important structural elements of moral acts (e.g., intention, causation, harm) but may not generalize to real-world judgments. As researchers have long shown, social judgments hinge on the identities (e.g., race, gender, age, religion, group affiliation) of both target and perceiver. Asking whether people generally condemn "shooting someone" is very different from asking whether liberals as opposed to conservatives condemn "a White police officer shooting a Black suspect." We argue for the importance of incorporating identity into moral psychology. We briefly outline the central role of identity in social judgments before reviewing current theories in moral psychology. We then advocate an expanded person-centered morality—synthesizing moral psychology with social cognition—to better capture everyday moral judgments.